Volcanic Hazards and Disasters in Human Antiquity 2000
DOI: 10.1130/0-8137-2345-0.33
|View full text |Cite
|
Sign up to set email alerts
|

Prehistoric "settlement crisis," environmental changes in the British Isles, and volcanic eruptions in Iceland: An exploration of plausible linkages

Abstract: Prehistoric volcanic eruptions in Iceland have been previously described as the most probable causes of several distinctive paleoenvironmental and archeological "events" in the British Isles. These events range in character from the development of sequences of extremely narrow growth rings in the Irish bog-oak tree-ring chronologies, to an inferred sudden abandonment of settlement in northern Scotland, an event sometimes termed the "Settlement Crisis" of the European Late Bronze Age. This chapter presents a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Elk and giant deer, the main prey animals of Federmesser hunters in Northern Europe, are closely tied to aquatic habitats (Geist, 1999) and they may have avoided areas affected by fall-out. However, it is unclear how extensive and persistent the impact of the LSE on the vegetation and climate was Litt et al, 2003) and it also has to be remembered that the impact of volcanic eruptions on human societies is often rather more indirect than through simple environmental change (e.g., Grattan and Gilbertson, 2000). Shennan (2000, p. 821) has suggested that 'the single most important factor in understanding culture change is population dynamics'.…”
Section: Resultsmentioning
confidence: 97%
“…Elk and giant deer, the main prey animals of Federmesser hunters in Northern Europe, are closely tied to aquatic habitats (Geist, 1999) and they may have avoided areas affected by fall-out. However, it is unclear how extensive and persistent the impact of the LSE on the vegetation and climate was Litt et al, 2003) and it also has to be remembered that the impact of volcanic eruptions on human societies is often rather more indirect than through simple environmental change (e.g., Grattan and Gilbertson, 2000). Shennan (2000, p. 821) has suggested that 'the single most important factor in understanding culture change is population dynamics'.…”
Section: Resultsmentioning
confidence: 97%
“…Anecdotal reports also speak of severe and ultimately lethal increases in dental wear as people and animals ingest tephra-laden vegetation (Trowbridge, 1976). Both the chemical load as well as the mechanical properties of distal tephra fall-out have contributed substantially to the direct and indirect impacts of other past eruptions (e.g., Edwards et al, 1994;Grattan and Gilbertson, 2000;Grattan et al, 2007Grattan et al, , 2005. Fluoride, with which the lower LST phase (LLST) -the one that participated preferentially in the distal NE fall-out -is 'extremely.enriched' (Harms and Schmincke, 2000, p. 90), causes enamel to soften (Fejerskov et al, 1988) and this may further compound already increased tooth wear due to mechanical abrasion.…”
Section: Discussionmentioning
confidence: 98%